PERSEPSI MASYARAKAT TERHADAP PELAYANAN PENDAFTARAN TANAH SECARA SPORADIK DI KANTOR PERTANAHAN KABUPATEN MINAHASA UTARA (Community Perception on Sporadic Land Registration Service at The Land Office of North Minahasa Regency) - Christiany Nissa Pelleng; Grace A. J. Rumagit; Theodora M. Katiandagho (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The objective of this research is to analyze community perceptions on sporadic land registration services at the Land Office of North Minahasa Regency. The research was conducted from July to December 2019. The data used in this study were primary data and secondary data. Primary data were obtained directly from the source directly through interviews/questionnaire filling out, namely people who did sporadic land registration at the Land Office of North Minahasa Regency. Meanwhile, secondary data was obtained through literature and scientific work documents related to the object of this research. The method used in this research is descriptive quantitative method using data from samples obtained from the research population and analyzed and described using statistical methods. The data analysis method used is a Likert Scale. Determination of the sample was carried out by purposive sampling, with the consideration that those who were selected were truly those who could answer the question, namely the people themselves without the power of a notary who submitted applications for land registration sporadically, which amounted to 65 people. The research results showed that the public's perception of sporadic land registration services at the Land Office of North Minahasa Regency was based on 10 service principles, namely the principle of simplicity, clarity, certainty of time, accuracy, security, responsibility, completeness of infrastructure, ease of access, discipline, courtesy, friendliness and comfort. , using 27 question indicators, the result of interpretation is 6454 and the result of the percentage level is 73.54% with a "good" interpretation. This means that the public's perception of sporadic land registration services at the North Minahasa Regency Land Office has received a good category. Public perception when viewed from each service principle, almost all of them already have a good perception interpretation value. There is only one service principle whose perception interpretation value is "good enough", namely the public's perception of the ease of access with an average perception score of 194.5 and the result of a percentage level of perception of 59.84%. Although currently the public's perception of sporadic land registration services is good, the North Minahasa Regency Land Office still needs 26.46% to improve its services so as to obtain an ideal or very good level of public perception.